Wastiary A bestiary of waste - Hennessy Picard, Michael; Brenchat Aguilar, Albert; Carroll, Timothy; Gilbert, Jane; Miller, Nicola (UCL Press, 2023)
Wastiary, or Bestiary of Waste, is a creative exercise that occupies letters, numbers, and symbols of Western academic language to compose a list of 35 short entries on the uncomfortable but pressing topic of waste in the contemporary world. The collection is richly illustrated with artwork, photography, collage and mixed media. The book is a heterodox compendium of 'beasts of waste', playfully re-imagining the medieval treatise on various kinds of animal. It conveys the message that various forms of waste and pollution have achieved a beast-like or untameable quality, at times pungently transferring to considerations of 'the human', or humans treated as waste.